13.6k views
1 vote
Rearrange the equation so x is the independent variable. -4x-6=-5y+9

User Lee Winder
by
6.6k points

2 Answers

2 votes

Answer:

The answer is y = 3 + 4/5x

Explanation:

Look at attachment:

Hope this helps! :)

Rearrange the equation so x is the independent variable. -4x-6=-5y+9-example-1
User Ksice
by
5.4k points
4 votes

Answer:

x =
(5y-15)/(4) or y = 3 + 4/5x

Explanation:

- 4 x - 6 = - 5 y + 9

(+ 6 on both sides)

- 4 x = - 5 y + 15

(รท -4 on both sides)

x =
(5y-15)/(4)

- 4 x - 6 = - 5 y + 9

( Add 4x to both sides to isolate -6 )

-6 = -5y + 9 + 4x

( Add 5y to both sides)

5y - 6 = 9 + 4x

( Minus 6 from both sides)

5y = 15 + 4x

y = 3 + 4/5x

User OctaviaLo
by
5.8k points